SAE Technical Paper Series 2006
DOI: 10.4271/2006-01-0685
|View full text |Cite
|
Sign up to set email alerts
|

A NOX Trap Study Using Fast Response Emission Analysers for Model Validation

Abstract: Lean burn after treatment systems using NO X traps for reducing emissions from diesel exhausts require periodic regeneration after each storage stage. Optimising these events is a challenging problem and a model capable of simulating these processes would be highly desirable. This study describes an experimental investigation, which has been designed for the purpose of validating a NO X trapping and regenerating model. A commercial computational fluid dynamics (CFD) package is used, to model NO X trapping and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…3(b) matches experimental data correctly. Improved tuning will be attempted when data are available from an ongoing experimental programme [18]. Fig.…”
Section: Particulate Trap Model; Methodology For Applying Equations Tmentioning
confidence: 99%
“…3(b) matches experimental data correctly. Improved tuning will be attempted when data are available from an ongoing experimental programme [18]. Fig.…”
Section: Particulate Trap Model; Methodology For Applying Equations Tmentioning
confidence: 99%
“…Several research groups have developed mathematical models to describe LNT performance [3,16,19,[21][22][23][24][25]. This research has demonstrated that there are multifarious factors that can influence NO x conversion efficiency, including exhaust gas composition and temperature, air-fuel ratio, the duration of the lean and rich cycles, and the composition of the BMO and noble metal type.…”
Section: Introductionmentioning
confidence: 98%
“…LNT behaviour has been studied in laboratory reactors using synthetic gases [2][3][4][5][6][7][8][9][10][11][12][13][14], on engine test beds [9,[15][16][17][18][19][20][21][22], and on vehicle drive cycle facilities [8,21,22]. Several research groups have developed mathematical models to describe LNT performance [3,16,19,[21][22][23][24][25]. This research has demonstrated that there are multifarious factors that can influence NO x conversion efficiency, including exhaust gas composition and temperature, air-fuel ratio, the duration of the lean and rich cycles, and the composition of the BMO and noble metal type.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the NO X sensor for SCR should not only meet the requirements of high accuracy and fast response, but also have low costs. Most of the current on-vehicle NO X sensors are working for steady-state conditions with high costs, and the fast response NO X detection system which has complicated structure with high costs is normally employed only in the lab [10,11]. Although many researches are focused on the NO emissions prediction for model-based control, the prediction model requires necessary assumptions as well and the accuracy of the model mainly depends on both the algorithms and support parameters [12,13].…”
Section: Introductionmentioning
confidence: 99%